Al-Qur’an antara Teks dan Konteks: The Qur'an between Text and Context - Hukmiah, Hukmiah; Sabri AR, Mohd (FAI UIM, 2024)
Qur'an is kalamullah or heavenly language that is down to earth so it requires a paradigm of thinking, both ways, methods and approaches. Qur'an which incidentally is the text makes some readers refer to the text or the literal meaning of the text without including the socio-historical context of the text in its interpretation activities, so that the determination of its meaning fully becomes the domain of the authority of the text. Outside the text there is no meaning that can be justified and believed to be true. Some other readers consider the need for a contextual approach to developing texts products, especially those relating to muamalah (social relations) and law. The most perfect understanding of verses is to pay attention to the social settings surrounding the descending verses. In other words, referring to the context dimension which is not solely based on the literal meaning of the text (literature), but also involves the socio-historical dimension of the text and the involvement of the interpreter's subjective subjectivity in its interpretation activities. Based on the discourse, this study would like to explain the urgency of the study of the Qur'an by combining textual with contextual methods, so that a comprehensive understanding of the texts of the Qur'an verses is found. This method considers the meaning in amr (command) and nahi (prohibition) of the nash (text), looking for illat (reason) if possible and considering the asliyat (the original meaning) and the tabi'iyat (the meaning that accompanies it).